Implementation of the Policy of Involving Bhabinkamtibmas as Investigators in Resolving Cases Through Restorative Justice at Sekongkang Police - Herman, Herman; Yamin, Ahmad; Dewi, Geatriana (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research discusses the implementation of the policy of involving Bhabinkamtibmas as investigators and investigators in resolving cases through restorative justice at the Sekongkang Police. The aim of this research is to describe the implementation of the policy of involving investigators and investigators in resolving cases through restorative justice at the Sekongkang Police. The type of research used in this research design uses a qualitative descriptive method with a comparative approach. The results found that the implementation of the Policy of Involving Bhabinkamtibmas as Investigators and Investigators in Resolving Cases Through Restorative Justice at the Sekongkang Police Station was based on George C. Edward III's Theory, namely a). Communication: by conveying messages, programs and ideas from the Sekongkang Police Chief to members of the criminal investigation unit and all members of the Sekongkang Police Department, West Sumbawa Police, with the aim being that every personnel from the criminal investigation unit and Sekongkang Police Headquarters understands the policy in its entirety, and can be accepted by all criminal investigation unit personnel. and the entire Sekongkang Police Department, Security and Security and Community Service and obtained increased case resolution results. The obstacle found is that there has not been a persuasive 2 (two) way communication so that there has been no direct feedback from the communicant, namely the investigator and investigator; b). Resources: there are different understandings regarding restorative justice related to explanations but they contain the same meaning, namely resolving cases through family means. The obstacle found was that of the three Bhabinkamtibmas people who were the research sample, only one Bhabinkamtibmas person had a first-degree education, besides that, not all Bhabinkamtibmas people had attended education and development of the criminal investigation function; c). Disposition or attitude: the implementor's attitude, support from leadership greatly influences policy implementers to achieve goals effectively and efficiently. The manifestation of this leadership support is placing policy as a policy priority, paying attention to the balance of region, religion, ethnicity, gender and other demographic characteristics. The obstacles found were the lack of motivation and commitment of members as investigators and investigators; d). Bureaucratic structure: Sekongkang Police does not yet have norms/guidelines in the form of Standard Operating Procedures (SOP) involving Bhabinkamtibmas as investigators and investigators. The obstacles found were the placement of bureaucrats who did not match their abilities, the ability of Bhabinkamtibmas in the fingerprint investigation process was still limited. So, it can be concluded that the implementation of the Policy for Involving Bhabinkamtibmas as Investigators and Investigators in Resolving Cases through Restorative Justice at the Sekongkang Police has not been fully implemented in accordance with standard SOPs for investigations and investigations and there are still obstacles found in communication factors, resources, disposition or attitude and organizational structure.